The Effect of Integrating Green Sustainable Science and Technology into STEM Learning on Students’ Environmental Literacy - Aye, May Zin (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study aims to explore the integration of Green Sustainable Science and Technology (GSST) in STEM learning to improve junior high school students’ environmental literacy through a project-based learning approach. Methodology: A qualitative case study design was employed. Data were collected through classroom observations, in-depth interviews with teachers and school officials, and document analysis. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing. Main Findings: The results show that teachers successfully integrated GSST into STEM learning through project-based activities, such as designing energy-saving devices using recycled materials. Students demonstrated high enthusiasm, gained meaningful learning experiences, and developed awareness of environmental protection. Supportive school policies and facilities further enhanced students’ conceptual understanding, environmental literacy, and positive attitudes toward sustainability. Novelty/Originality of this study: This study introduces GSST integration into STEM learning at the secondary school level as an innovative model to enhance environmental literacy. The novelty lies in linking sustainability with practical project-based approaches, advancing educational practices that foster both conceptual mastery and environmental responsibility to support sustainable education.